Emotion Recognition and Regulation using Multi-Model System - M. Vijayalakshmi, Abishek Balasubramanian, Swapnil Satpute (International Journal of Advanced Science and Technology, 2020)
Older age is normatively associated with losses in cognitive, physical and social domains. Detection of emotion of people at old age homes is therefore important, as it can help suggest ideas and ways to tackle everyday life muddle. This work proposes a model to detect the emotional state of the people by facial expressions and speech. The emotion, if detected to be negative, will capture an image and send it to the helpers directing their attention towards the individual. The system will then request a name and display the history, hobbies and likings of the individual from the database to help regulate the emotion of the individual.Keywords: Emotion recognition, Facial expressions, Speech, Emotion Regulation, Old age individuals.